Providing a Model for Predicting Couples’ Emotional Divorce Based on Metacognitive Beliefs and Emotional Regulation Strategies Mediated by Marital Burnout in Married Women - Sarkhabi Abdolmaleki, Maryam; Dokanei Fard, Farideh; Behbodi, Masomeh (Applied Family Therapy Journal (AFTJ), 2021)
Aim: The present study aimed to provide a model for the prediction of the couple’s emotional divorce based on attachment styles, metacognitive beliefs, and emotional regulation strategies mediated by marital burnout in married women. Methods: The present study was descriptive-correlational and exploratory sequential and directed with a statistical population of 1854 married women who visited health houses of Tehran in 2019. We selected 375 women using the multi-stage random sampling method and sample power software. The research tools included Gottman Emotional Divorce Scale (EDS) (2008), the metacognition questionnaire by Wells et al. (2004), the emotional cognitive regulation strategy questionnaire by Garnefski et al. (2001), and the marital burnout scale by Pines (1966) that were conducted on the samples. We utilized structural equations SmartPLS (partial least squares) in addition to descriptive statistical indices to analyze data. Results: The results of standard coefficients of direct path analysis indicated that there was a significant relationship between metacognitive beliefs (β=0.650) and emotional regulation strategies (β=-0.944) with emotional divorce. Furthermore, the results of standard coefficients of the indirect path indicated appropriate relationships between metacognitive beliefs (β=0.618) and emotional regulation strategies (β=0.694) mediated by marital burnout with emotional divorce in married women. Conclusion: According to research findings, the family counselors are suggested using the confrontation of internal psychological elements to improve couples’ relationships during their treatment and to create cohesion and a conscious relationship.